THE EFFECT OF MULTIMEDIA ON KNOWLEDGE AND ATTITUDE OF HIGH SCHOOL STUDENTS ABOUT EXCLUSIVE BREASTFEED - Bhernia Indri Setyowati; Sri Achadi Nugraheni; Farid Agushybana (Faculty of Public Health, Andalas University, 2018)
Adolescent reproductive health education contributes the enhancement of knowledge, attitudes and behaviors of exclusive breastfeeding as later mothers. Multimedia is used to its improve . The aim is to knowing the effect of multimedia on knowledge and attitude of schoolgirls about exclusive breastfeeding. Quantitative research with non-randomized control group pretest-posttest design. With 104 schoolgirls respondents in Semarang district Indonesia as a control and intervention group, processed by one way repeated measures ANOVA.The results of the study showed the influence of multimedia in improving knowledge and attitude about exclusive breastfeeding. The average score of knowledge of the intervention group increased by 4,077 from pretest to posttest 2 and control group knowledge decreased 0.48 from pretest to posttest 2. The average score of attitude of the intervention group increased 5,308 from pretest to posttest 2 and control group decreased 2,519 from pretest to posttest 2.Statistically, multimedia (p = 0,000) had an effect on improving knowledge and attitudes about exclusive breastfeeding between before and after intervention. Based on the results of this study, health and education institutions are expected to develop multimedia as an effort to implement the IEC program on exclusive breastfeeding and integrate with school activities.